Influência do perfil em ácidos graxos nas propriedades de biodieseis de óleos usados de fritura e de suas blendas com biodiesel de Attalea maripa - Xavier, Luciana Araújo (2013)
Extensive studies about the biodiesel show their several advantages, however the different types of biodiesels obtained by different raw materials can to result in disadvantages and canto produce a biodiesel unviable for the use. Thus, the aim of this study is to evaluate biodiesels produced from different used frying oils (UFOs), that are an economical choice, due the their low costs, as well as evaluating the effects of blends of used frying oil biodiesel and inajá oil biodiesel in the properties of biodiesel. The oil from inajá it's a promising source for biodiesel production, because the almond display a high percentage of oil. The methylc biodiesels were produced by transesterification using alkaline catalyst, their fatty acid profile, free glycerine content and mono-, di- and triglycerides content were analyzed by gas chromatography with flame ionization detector (GC-FID). All the properties of the biodiesels were determined following standard methods in accordance with the ANP Standard. Were collected eleven different used frying oils, the GC-FID results displayed small variation in their fatty acid profile. Ten UFOs showed as major components, the methyl linoleate and methyl oleate, respectively. Only one UFO displayed as major components, the methyl oleate and methyl palmitate. Despite similarity in fatty acid profile of the UFOs, there is a large variation in their properties of the biodiesels, which could not be justified in its entirety by the fatty acid composition. This suggests that components derived from thermal degradation, can to influence on the properties of the biodiesel. However the oxidation stability can be correlated with the fatty acid profile, thus only the sample with high content of saturated, displayed a higher oxidative stability. The blends of used frying oil biodiesel and inajá oil biodiesel displayed different fatty acid profile. The inajá oil biodiesel showed as major components, the methyl laureate and methyl myristate respectively. Thus, the blends resulted in a reduction of unsaturated esters and higher esters of short chain saturated. Only the properties of the blend of biodiesel with 50% v/v of the two biodiesels were analyzed. This blend displayed best results for the properties of biodiesel in compared to pure inajá oil biodiesel, a higher oxidative stability and smaller acid number than the pure UFO biodiesel, however displayed a low flash point. This study showed that the presence of thermal degradation compounds in the used frying oils can affect the properties of biodiesel. However, the frying oils collected in Boa Vista displayed a good quality, resulting in a biodiesel within the limit established by the ANP. The inajá oil biodiesel displayed several properties outside the limit set by the ANP, becoming unviable their use as biodiesel. The blends of the two biodiesels are promising for the correction of the properties of the biodiesel in relation to pure biodiesels.